2022
DOI: 10.3389/fphar.2022.992731
|View full text |Cite
|
Sign up to set email alerts
|

Dupilumab efficacy and safety in patients with moderate to severe asthma: A systematic review and meta-analysis

Abstract: Background: Dupilumab is a human monoclonal antibody directed against the alpha subunit of the interleukin-4 receptor and inhibits the signaling of IL-4 and IL-13. It is approved for treating asthma and other type-2 inflammatory diseases. There is a conflict in the literature regarding the safety and efficacy of dupilumab. Thus, we aimed to assess the safety and efficacy of dupilumab in patients with moderate to severe asthma.Methods: Six databases (PubMed, Embase, Scopus, Web of Science, Cochrane library, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 50 publications
(157 reference statements)
0
1
0
Order By: Relevance
“…Dupilumab is a humanized IgG4 monoclonal antibody that targets the IL-4Rα chain, which has been officially approved for several type 2 inflammatory diseases, including moderate to severe atopic dermatitis (AD) [90][91][92], moderate-to-severe eosinophilic or oral steroid-dependent asthma [93,94], inadequately controlled CRSwNP [95,96] and aspirin-exacerbated respiratory disease [97,98]. Since the first proof-of-concept study of dupilumab was reported in 2016, 25 clinical trials have been conducted on CRSwNP worldwide, which have demonstrated broad efficacy in CRSwNP management [99].…”
Section: Dupilumabmentioning
confidence: 99%
“…Dupilumab is a humanized IgG4 monoclonal antibody that targets the IL-4Rα chain, which has been officially approved for several type 2 inflammatory diseases, including moderate to severe atopic dermatitis (AD) [90][91][92], moderate-to-severe eosinophilic or oral steroid-dependent asthma [93,94], inadequately controlled CRSwNP [95,96] and aspirin-exacerbated respiratory disease [97,98]. Since the first proof-of-concept study of dupilumab was reported in 2016, 25 clinical trials have been conducted on CRSwNP worldwide, which have demonstrated broad efficacy in CRSwNP management [99].…”
Section: Dupilumabmentioning
confidence: 99%
“…Robust clinical trial evidence has demonstrated that for appropriately selected patients, the addition of a biologic asthma therapy to a patient's existing moderate-dose ICS and LABA regimen results in significant reductions in exacerbations and use of oral corticosteroids, and improved asthma symptom control and quality of life, though there are only modest improvements in lung function. [29][30][31][32][33] Table 1 provides a comparison of biologic therapies for severe asthma, including efficacy data.…”
Section: Severe Asthma With Evidence Of Persistent Type 2 Inflammatio...mentioning
confidence: 99%
“…An IL-4Rα targeted biologic agent, blocking the effects of IL-4 and IL-13, contributes to the reduction in different markers from T2 inflammation, including FENO, IgE, periostin, and eotaxin-3, among others. Dupilumab could also improve antiviral immune response in patients with severe T2 asthma on account of IL-4 and IL-13 by damaging the production of viral-induced IFN that expresses TLR3 [4,101].…”
Section: Dupilumabmentioning
confidence: 99%